Pemberian Edukasi Berbasis Teori Betty Neuman untuk Meningkatkan Kesiapan Pasien dalam Menghadapi Operasi - Sari, Yunita Indah; Yuswanto, Tri Johan Agus (FORIKES, 2025)
Patients undergoing surgery often experience fear and anxiety, which can affect their preparedness. Preoperative education is expected to improve patient preparedness. The purpose of this study was to analyze the effect of Betty Neuman's theory-based education on patient preparedness for surgery in the hospital. This study used a two-group pretest–posttest design. A total of 112 respondents were selected using a simple random sampling technique. Patient preparedness was measured by completing a questionnaire. Data analysis was performed using the Wilcoxon and Mann–Whitney tests. The results of the hypothesis test regarding differences in patient preparedness for surgery in the control and intervention groups showed a p-value of 0.001 for administrative, physical, and mental preparedness, indicating a difference in patient preparedness for surgery between the groups. In this case, after receiving Betty Neuman's theory-based education, patient preparedness improved. The conclusion of this study states that Betty Neuman's theory-based education is effective in improving patient preparedness for surgery.Keywords: Betty Neuman's theory; education; patient preparedness; preoperative ABSTRAK Pasien yang akan menjalani operasi sering mengalami ketakutan dan kecemasan yang dapat memengaruhi kesiapan pasien. Edukasi praoperasi diharapkan dapat meningkatkan kesiapan pasien. Tujuan penelitian ini adalah menganalisis pengaruh edukasi berbasis teori Betty Neuman terhadap kesiapan pasien dalam menghadapi operasi di rumah sakit. Penelitian ini menggunakan desain two-group pretest–posttest. Sebanyak 112 responden dipilih menggunakan teknik simple random sampling. Kesiapan pasien diukur melalui pengisian kuesioner. Analisis data dilakukan menggunakan uji Wilcoxon dan Mann–Whitney. Hasil uji hipotesis tentang perbedaan kesiapan pasien dalam menghadapi operasi pada kelompok kontrol dan kelompok intervensi menunjukkan nilai p = 0,001 pada kesiapan administrasi, fisik, dan mental, yang artinya ada perbedaan kesiapan pasien dalam menghadapi operasi antara kelompok. Dalam hal ini, setelah diberikan edukasi berbasis teori Betty Neuman terbentuk kesiapan pasien yang lebih baik. Kesimpulan penelitian ini menyatakan bahwa edukasi berbasis teori Betty Neuman efektif untuk meningkatkan kesiapan pasien dalam menghadapi operasi.Kata kunci: teori Betty Neuman; edukasi; kesiapan pasien; pra operasi